Phytochemical Screening, Biological Studiesand GC-MS Analysis of Extract of Biden pilosa L - Khanal, Dharma Prasad; Rana, Rupa; Raut, Bechan; Dhakal, Rabindra Prasad (Journal of Manmohan Memorial Institute of Health Sciences, 2019)
Objective: The aim of the research work was to carry out the extraction of areal parts of Biden pilosa L by hydroalcholic and Hexane, ethyl acetate and acetone mixture followed by qualitative phytochemical analysis, acute oral toxicity test, anti-inflammatory test and GC-MS analysis of the extracts. Method: The hydro-alcoholic and HEA(n-hexane, ethyl acetate and acetone) extraction was done from aerial parts using ethanol and water in the ratio 70:30 and n-hexane, ethyl acetate and acetone in the ratio of 1:1:1 (HEA extract) respectively. Acute oral toxicity testwas performed OECD guidelines. The single spot in TLC was obtained using n-hexane as solvent for HEA fraction and finally phytocomponents were identified by GC-MS present in that spot.In vitro anti-inflammatory activity was performed by human RBC membrane stabilization method. Result: The phytochemical test results obtained indicate that hydro-alcoholic extract of aerial part of Bidens pilosa L. possess alkaloids, tannins, terpenoids and saponins whereas HEA extract possess alkaloids, flavonoids, tannins. Both hydro-alcoholic and HEA extracts were found to be safe up to the dose of 2000 mg/kg BW of the mice. Both extracts showed significant in vitro anti-inflammatory activity in a concentration dependent manner. The GC-MS analysis of HEA extract of aerial parts showed the presence of the sixteen different compounds from partially separated extract from TLC plates. Conclusion: Hydro-alcoholic extract of aerial part of Bidens pilosa L. possess alkaloids, tannins, terpenoids and saponins whereas HEA extract possess alkaloids, flavonoids, tannins. Both hydro-alcoholic and HEA extracts were found to be safe up to the dose of 2000 mg/kg BW of the mice. The GC-MS analysis of HEA extract of aerial parts showed the presence of the sixteen different compounds.